Central and peripheral fatigue during passive and exercise-induced hyperthermia - Periard, J. D.; Caillaud, C.; Thompson, M. W. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Hyperthermia was induced during prolonged exercise (ExH) and passive heating (PaH) to isolate the influence of exercise on neuromuscular function during a maximal voluntary isometric contraction (MVC) of the quadriceps under heat stress. The influence of cardiovascular strain in limiting endurance performance in the heat was also examined.